Pemaknaan Khalayak Terhadap Keragaman Budaya Indonesia Dalam Musik Video Wonderland Indonesia 2 : The Sacred Nusantara (Chapter 2) Karya Alffy Rev - Rasyid Farhan Taufik, Mohammad; Lestari, Sri Budi; Naryoso, Agus (Interaksi Online, 2024)
Indonesia is renowned for its cultural diversity, encompassing various ethnic groups, languages, cultures, and religions. According to the 2010 Population Census by the Central Statistics Agency, there are 1,340 ethnic groups and 720 languages. However, the 2020 Population Census revealed a decline in the use of regional languages among the younger generation. This cultural diversity is showcased in the music video "Wonderland Indonesia 2: The Sacred Nusantara (Chapter 2)" by Alffy Rev. Preliminary research on the viewers’ reactions and comments indicates that audiences often struggle to grasp the messages and meanings behind the representation of Indonesia’s cultural diversity directly. This study aims to understand how viewers interpret the cultural diversity of Indonesia as portrayed in the music video "Wonderland Indonesia 2: The Sacred Nusantara (Chapter 2)." This research employs a constructivist paradigm, utilizing representation theory and Kluckhohn’s cultural elements, which include the language system, knowledge system, kinship and social organization system, living equipment and technology system, economic system, religious system, and art. The study adopts an audience meaning analysis approach to comprehend the viewers' interpretations and positioning regarding the cultural messages conveyed, based on Stuart Hall's three positions of decoding: Dominant, Negotiated, and Oppositional. The findings indicate that the audience has diverse interpretations of this music video, influenced by their cultural backgrounds and knowledge. Most informants adopt a dominant position in interpreting the cultural diversity of Indonesia; however, some informants have differing and critical interpretations of the dominant meaning